(untitled) (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2013)
Chlorpyrifos is a hazardous insecticide and important pollutant of the environment. The EU Directive 2008/105/EC lists it as one of the priority water pollutants. Its presence is mainly detected by chemical methods but, since biological tests have gained in importance in the last few years, this study aimed to assess the potentials of white mustard (Sinapis alba L.) and maize (Zea mays L.) as indicators of water pollution. The phytotoxic effects of chlorpyrifos (rates 0.05-10µg a.i./l) were assessed based on physiological (germination energy and germination) and morphological traits (root and shoot length, fresh and dry weights) of the tested species. A slightly modified filter paper method was used and the results were processed by Duncan`s multiple range test and Probit analysis (EC50). According to the Directive, the maximal allowable concentration (MAC) of chlorpyrifos in water is 0.1µg a.i./l. When applied at the MAC value, chlorpyrifos inhibited germination energy and germination (11.25%) of white mustard, as compared to the control (91.5; 93.5%), and its hypocotyls and epicotyls failed to form. At the rates 50% below the MAC, germination energy and germination (87.75; 88.25%) were significanty inhibited, as well as root and shoot growth of seedlings. Chlorpyrofos did not affect the germination energy and germination of maize, while all morphological traits were significantly reduced by chlorpyrifos at the MAC rate. The EC50 of chlorpyrifos was 0.09µg a.i./l for germination of white mustard and 3.21µg a.i./l for maize.